The effect of diabetes education on maternal and neonatal outcomes in pregnant women diagnosed with gestational diabetes - Serap Topkara; Çağanay Soysal (BMC Pregnancy and Childbirth)
Abstract Background Education during pregnancy is important for the development of the pregnant woman’s ability to adapt to change and for a healthy birth. In this study, we aimed to examine the effects of education through a diabetes education program on maternal and newborn health in women diagnosed with gestational diabetes. Materials and methods In our study, we compared the maternal and neonatal health outcomes of pregnant women who participated in the diabetes education program and were diagnosed with gestational diabetes with the outcomes of pregnant women who did not participate in the diabetes education program and were diagnosed with gestational diabetes. The study included patients who were diagnosed with diabetes between 24and 26 weeks gestation at a tertiary education and research hospital and who underwent a 75-gram OGTT test. Age, BMI, parity, method of delivery, weight gain during pregnancy, newborn birth weight, gestational age and Apgar scores were compared. Results The study included 119 patients and analyzed maternal-neonatal outcomes. There were no statistically significant differences in age (33 ± 5.7 versus 31 ± 5.2), body mass index (BMI) (32.2 vs. 31.2), gravidity, parity, number of miscarriages, mode of delivery, family history of diabetes, smoking, prenatal corticosteroid use, and gestational age at delivery. The HbA1c value (p: 0.013), the total weight gain during pregnancy (p: 0.015), the need for insulin treatment (p: 0.002), and the birth weight (0.005) were significantly higher in the group without diabetes education. Conclusion In our study, diabetic school education was associated with lower HbA1c levels, less weight gain and less need for insulin therapy. When the results were categorized by insulin use, it was found that in patients using insulin, those who received diabetic school education had fewer macrosomic fetuses, whereas in patients not using insulin, those who received diabetic school education had lower maternal weight gain during pregnancy.